Is It Possible to Differentiate Chronic Kidney Disease and Preeclampsia by means of New and Old Biomarkers? A Prospective Study. (8th October 2015) - Rolfo, Alessandro; Attini, Rossella; Tavassoli, Elisabetta; Vigotti Neve, Federica; Nigra, Marco; Cicilano, Matteo; Nuzzo, Anna Maria; Giuffrida, Domenica; Biolcati, Marilisa; Nichelatti, Michele; Gaglioti, Pietro; Todros, Tullia; et al.
Abstract : Objective . Chronic kidney disease (CKD) and preeclampsia (PE) may both present with hypertension and proteinuria in pregnancy. Our objective is to test the possibility of distinguishing CKD from PE by means of uteroplacental flows and maternal circulating sFlt-1/PlGF ratio. Design . Prospective analysis. Population . Seventy-six patients (35 CKD, 24 PE, and 17 other hypertensive disorders), with at least one sFlt-1/PlGF and Doppler evaluation after the 20th gestational week. Methods . Maternal sFlt-1-PlGF were determined by immunoassays. Abnormal uterine artery Doppler was defined as resistance index ≥ 0.58. Umbilical Doppler was defined with gestational-age-adjusted Pulsatility Index. Clinical diagnosis was considered as reference. Performance of Doppler study was assessed by sensitivity analysis; sFlt-1/PlGF cut-off values were determined by ROC curves. Results . The lowest sFlt-1/PlGF ratio (8.29) was detected in CKD, the highest in PE (317.32) (P < 0.001 ). Uteroplacental flows were mostly preserved in CKD patients in contrast to PE (P < 0.001 ). ROC analysis suggested two cut-points: sFlt-1/PlGF ≥ 32.81 (sensitivity 82.93%; specificity 91.43%) and sFlt-1/PlGF ≥ 78.75 (sensitivity 62.89%, specificity 97.14%). Specificity reached 100% at sFlt-1/PlGF ≥ 142.21 (sensitivity: 48.8%). Early-preterm delivery was associated with higher sFlt-1/PlGF ratio and abnormal uteroplacental flows relative to late-preterm and term deliveries. Conclusions . sFlt-1/PlGF ratio and uteroplacental flows significantly correlated with PE or CKD and preterm delivery.